PENGARUH KINERJA KEUANGAN (UMKM), PELATIHAN KEWIRAUSAHAAN DAN JARINGAN PEMASARAN TERHADAP PERTUMBUHAN EKONOMI MASYARAKAT DI KABUPATEN SLEMAN, KECAMATAN PAKEM, DESA PAKEMBINANGUN - Benedikta Oren Hurit; Hasim As’ari (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the influence of Micro, Small, and Medium Enterprises (MSMEs) financial performance, entrepreneurship training, and marketing network on community economic growth in Pakembinangun Village, Pakem District, Sleman Regency. The research employed a qualitative research method with an interpretive approach, emphasizing the understanding of meaning, uniqueness, and in-depth hypothesis discovery through the triangulation of data collection techniques, including observation, interviews, and questionnaires. The population for this study encompassed all MSME owners in Pakembinangun Village, Pakem District, Sleman Regency, Special Region of Yogyakarta. The sample size was determined using the Hair et al. formula, resulting in 100 respondents for the study. The analysis method applied was multiple linear regression. The findings indicate that two variables have a significant influence on local economic growth: Financial Performance (MSMEs) and Marketing Network, with the marketing network providing the largest contribution. Conversely, the entrepreneurship training variable was found to have a negative effect on economic development. These results hold important implications for community economic empowerment policies at the village level.